Elevator controller based on implementing a random access memory in FPGA - Azzad Bader Saeed (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Previous techniques of elevator controllers suffer from two main challenges: processing time, and software size. In this work these challenges have been overcame by implementing a controller random access memory (RAM) in a fast FPGA for a proto-type of two-floors elevator, as known the RAM and FPGA are fast devices. A look-up-table LUT (which is fast technique) has been proposed for this work, this LUT has represented a proposed relation between 10 and 7 lines, the states of the sensors and switches have been represented by the 10 input lines, and the commands for the motors of slide door and traction machine have been represented by the 7 output lines. The proposed LUT has been schematically realize by a (10×7) bits RAM which has been implemented in field programmable gate arrays (FPGA). The proposed system has been performed using 'ISE Design Suit' software package and FPGA Spartan6 SP-605 evaluation kit, the clock frequency of this FPGA is 200 MHz which is respectively high. The processing time and software size of the proposed controller had reached to 20ns and 3.75 MB, which they are less than that obtained from the results of previous techniques.